Daily and seasonal rhythmic secretary pattern of antioxidant and oxidative stress biomarkers in mithun bull - PERUMAL, P; VIKRAM, R; HUSEN, M N SADDAM; KHAN, M H (The Indian Journal of Animal Sciences, 2022)
A study was conducted to assess the rhythmic changes of antioxidant and oxidative stress profiles (antioxidantand oxidative stressors together is called as oxidative stress biomarkers: OSBs) to understand their flow pattern in24 h during different seasons (winter, spring, summer and autumn) in intact adult mithun bulls (n=6; 5–6 years).Antioxidants [total antioxidant capacity (TAC), superoxide dismutase (SOD), glutathione (GSH), glutathionereductase (GSHR) and catalase (CAT)] and oxidative stressor [malondialdehyde (MDA)] were estimated at 4 hinterval for a whole day in different seasons. Analysis was done in two different ways with respect to time (0800,1200, 1600, 2000, 2400 and 0400 h) and day time (0800 to 1600 h) and night time (2000 to 0400 h) collections. Thelevels of OSBs differed significantly among the seasons, among the collection times and between day and nighttimes. Winter and spring had recorded significantly higher antioxidants and lower MDA than summer. Levels ofantioxidants were higher and MDA was lower during night as compared to day time collections. It was concludedthat spring and winter seasons had greater beneficial effects than summer on health and wellbeing of the mithun.